THE EFFECTIVENESS OF HOTEL TAX REVENUE TO INCREASING REGIONAL OWN INCOME (PAD) IN THE CITY OF PAREPARE - putri, ade; Riska, Rina; said, zainal (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2023)
Hotel tax is one part of the regional tax that has the potential to receive Regional Original Revenue for the City of Parepare. The development of the hotel industry will have a direct impact on increasing Local Own Revenue, this is a challenge for the City Government of Parepare to further extract revenue from the existing hotel tax sector. This study aims to determine the potential for hotel taxes to increase PAD in Parepare City, to determine the factors that influence hotel tax revenue to increase in PAD in Parepare City, and to determine efforts to achieve hotel tax results for increasing PAD in Parepare City. This study uses qualitative methods and in collecting data using a phenomenological approach. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Test the validity of the data used in this study is a test of credibility. The results of this study indicate that the Parepare City Government has been quite effective in realizing the existing hotel tax revenue budget during 2018-2019 where the amount of realization has reached the predetermined target, except in 2020 it could not be realized due to the Covid-19 pandemic. It's just that in exploring the potential for hotel taxes, the Parepare City government is still not effective because the potential for hotel taxes is very large when compared to the actual hotel tax revenue that occurs. In 2018 the realization of hotel tax revenue was only IDR 1,108,908,632, very far from the potential revenue from the survey results of IDR 6,613,978,229. In 2019 the total realized hotel tax revenue was only 1,364,197,552 with a total potential revenue of 6,497,191,314 rupiah. Whereas in 2020 the amount of realized revenue is relatively small, only 776,381,615 rupiah, with the potential amount of 6,117,467,628 rupiah.